A Setup for Preparation of Glass-Carbon Coatings on TiO2-Nb2O5 Intended for Hip Joint Prostheses - Jordan GEORGIEV; Stefan STEFANOV; Dimitar TEODOSIEV; Lubomir ANESTIEV (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2010)
A setup for preparation of glass-carbon coatings on TiO2-Nb2O5 ceramic materials, intended for implants for surgery of hip joint prostheses, is described. The setup described consists of vacuum tight ceramic chamber; programmable high temperature furnace and a system for controlled introduction of inert gas into the chamber. The setup allows working with temperatures up to 1350 oC, controlled heating rates from 1 to 15 oC/min and chamber pressures down to 10-2 mmHg.